2020
DOI: 10.1111/aab.12650
|View full text |Cite
|
Sign up to set email alerts
|

Vole activity surveys predict damage to cover‐cropped soybean plants

Abstract: Across the Midwestern United States, farmers have increasingly used winter cover crops in corn-soybean rotations to improve soil health. Although this practice has many benefits, it also can provide habitat for potential pest species, such as voles (Microtus pennsylvanicus and M. ochrogaster). Voles have been reported by farmers to damage soybean plants in fields which had recently been cover cropped, but little has been done to quantify levels of damage related to their abundance. We evaluated the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Within our study area, deer mice ( Peromyscus maniculatus ) and prairie voles ( Microtus ochrogaster ) were commonly found in row‐crop agricultural fields (Berl, Flaherty, Danielson, Kellner, & Swihart, 2017), while additional species, such as meadow voles ( Microtus pennsylvanicus ) and northern short‐tailed shrews ( Blarina brevicauda ), were identified in adjacent permanent herbaceous habitats such as field borders or in‐field grass waterways (Prieur, 2019). Other potential prey items included avian prey (e.g., small passerines such as horned larks ( Eremophila alpestris ) and Lapland longspurs ( Calcarius lapponicus ) as well as larger species, such as killdeer ( Charadrius vociferus ) and blackbirds (Icteridae, personal observation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within our study area, deer mice ( Peromyscus maniculatus ) and prairie voles ( Microtus ochrogaster ) were commonly found in row‐crop agricultural fields (Berl, Flaherty, Danielson, Kellner, & Swihart, 2017), while additional species, such as meadow voles ( Microtus pennsylvanicus ) and northern short‐tailed shrews ( Blarina brevicauda ), were identified in adjacent permanent herbaceous habitats such as field borders or in‐field grass waterways (Prieur, 2019). Other potential prey items included avian prey (e.g., small passerines such as horned larks ( Eremophila alpestris ) and Lapland longspurs ( Calcarius lapponicus ) as well as larger species, such as killdeer ( Charadrius vociferus ) and blackbirds (Icteridae, personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…Small mammal populations in our area were likely in a low phase during the 2 years of our study. A concurrent study (Prieur, 2019) observed low levels of vole damage to soybeans (0–14.1%) and had low trap success, while a regional study of northern harriers ( Circus hudsonius ), which are considered vole specialists in the Midwest, found relatively low levels of voles in harrier diets during the same time period (Zagorski, 2019).…”
Section: Methodsmentioning
confidence: 99%